ASIMETRI INFORMASI; UNDERWRITER DAN EARNING MANAGEMENT HUBUNGANNYA TERHADAP INITIAL RETURN (STUDI EMPIRIS PADA IPO DI INDONESIA) - Muhammad Fahmi; Muhammad Irsan (ITB AAS INDONESIA, 2023)
The purpose of this study is to examine whether the underwriter creates information asymmetry in order to determine the balance of initial returns, and whether there are indications of earning management practices in the implementation of the IPO. This study is a deductive quantitative study, with 175 IPO companies on the IDX for the 2016-2022 period as the sample. This study used path analysis techniques by testing the hypothesis with the Sobel formulation. This study found empirical evidence that underwriters performed information asymmetry in order to determine the balance of positive initial returns. However, there is no empirical evidence that managers performed earning management through discretionary accruals in order to determine the balance of positive initial returns on the implementation of the IPO.